Insecticide resistance status of three vectors of Japanese encephalitis in east central India. Issue 2 (18th December 2018) - Sahu, S. S.; Sonia, T.; Dash, S.; Gunasekaran, K.; Jambulingam, P.
Abstract: Japanese encephalitis (JE) has been reported in different districts of Odisha state (east central India) since 1992. During 2016, a major outbreak of JE and acute encephalitis syndrome (AES) occurred in the Malkangiri district of Odisha, causing 103 deaths in children, of which 37 were caused by JE and 66 by AES. Information on insecticide resistance in JE vectors is important for the selection of appropriate insecticides for use in vector control. The present study was designed to determine the resistance status of three important vectors of JE, Culex vishnui, Culex tritaeniorhynchus and Culex bitaeniorhynchus (Diptera: Culicidae), against dichlorodiphenyltrichloroethane (DDT), malathion and deltamethrin in three districts of Odisha state affected by JE. Female adult mosquitoes were collected using mouth aspirators both indoors and outdoors in JE‐affected villages and used in susceptibility bioassays following World Health Organization guidelines. Knock‐downs were recorded every 10 min up to 1 h and mortality rates were recorded at 24 h post‐exposure. Culex vishnui and Cx. tritaeniorhynchus showed resistance to DDT, malathion and deltamethrin, whereas Cx. bitaeniorhynchus was susceptible in all study districts. The information generated by this study will be highly useful in the planning and implementing of appropriate vector control operations for the prevention and control of JE in east central India. Abstract : Culex vishnui was resistant to DDT, malathion and deltamethrin in all three study districts, but not to deltamethrin in Koraput district, where it was classified as showing 'possible resistance'. Culex tritaeniorhynchus was highly tolerant of all three insecticides tested in all three study districts. Culex bitaeniorhynchus was susceptible to DDT, malathion and deltamethrin across all three study districts.